2004
DOI: 10.1128/mcb.24.24.10584-10592.2004
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between MITF, PIAS3, and STAT3 in Mast Cells and Melanocytes

Abstract: Microphthalmia transcription factor (MITF) and STAT3 are two transcription factors that play a major role in the regulation of growth and function in mast cells and melanocytes. In the present study, we explored the MITF-PIAS3-STAT3 network of interactions, how these interactions regulate gene expression, and how cytokine-mediated phosphorylation of MITF and STAT3 is involved in the in vivo interplay between these three proteins. In NIH 3T3 cells stimulated via gp130 receptor, transfected MITF was found to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
1
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 49 publications
2
63
1
1
Order By: Relevance
“…For instance, the ring finger domain has been shown to be important for PIAS3's activity as a sumo-E3 ligase (21,23). We have found that PIAS3 functions in vivo as a key molecule in suppressing the transcriptional activity of both MITF and STAT3 (10,24,25). More specifically, we demonstrated that following cellular activation, PIAS3 is released from MITF and binds to STAT3 (25).…”
mentioning
confidence: 72%
“…For instance, the ring finger domain has been shown to be important for PIAS3's activity as a sumo-E3 ligase (21,23). We have found that PIAS3 functions in vivo as a key molecule in suppressing the transcriptional activity of both MITF and STAT3 (10,24,25). More specifically, we demonstrated that following cellular activation, PIAS3 is released from MITF and binds to STAT3 (25).…”
mentioning
confidence: 72%
“…In the nucleus of resting cells, unphosphorylated Mitf is inactivated by association with PIAS3. Activation of the gp130 receptor or c-Kit receptor in melanoma and mast cells induces Mitf phosphorylation and results in the release of PIAS3, which then binds STAT3 (37,38). This indicates that the phosphorylation and dephosphorylation of Mitf is a key step in the regulation of interaction between Mitf, PIAS3, and STAT3.…”
Section: Discussionmentioning
confidence: 99%
“…This does not confirm previously published studies of the group of Razin. These investigators described the NH 2 terminus of mPIAS3 as the major STAT3 interaction domain (29,38). The discrepancies between the data might be due to different methods used in the interaction analyses, the use of different cell types, and different PIAS3 variants.…”
Section: Discussionmentioning
confidence: 99%
“…It was therefore reasonable to postulate that PIAS3 and STAT3 might interact through similar domains. However, a previous report showed that an NH 2 -terminal fragment of mPIAS3, comprising amino acid positions 82 to 132, interacts with STAT3 in murine cell lines (15,29). We performed yeast two-hybrid analyses with the NH 2 terminal (amino acid positions 1-319) and the COOH terminal (amino acid positions 320-619) fragments of hPIAS3.…”
Section: Delimitation Of the Pias3 And Stat3 Interaction Domainsmentioning
confidence: 99%